Forensic Age Estimation in Swiss Asylum Procedures: Race in the production of age - Oertli, Johannes Balthasar (Refuge, 2019)
In asylum procedures, authorities often doubt the claim of an unaccompanied young person to be a child. In Switzerland, in such cases, asylum seekers are made to undergo forensic age estimation to assess their “actual” age. This article studies this practice, drawing on interviews with the people who commission and conduct it. It elaborates on what triggers such “age disputes” and explains how age is being assessed. It continues by highlighting the difference between forensic and medical age estimation and how the use of FAE in a forensic environment racializes the children involved. In conclusion, this article reflects on the meaning of this racialization and what it, as well as the use of FAE, signifies about the interplay of racialized boundaries and legal borders within current migration regimes.